(3QjGV GdSfHd hMjGV ChQGb GdJfHd GdeTJedI Ydi eaQMGJ NhGU YQhb GdMRfHds - (3GdgfOj, Gdjefj, GdCfUGQj, SYO GdOjf Hf gHI Gddg Hf YHO GdQMje Hf LYaQ ; cGf MjG(B1306(3g`s
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdbOhS adeG GSJbQ aj GddhGA befOGfG ceG ojQGO CgOi Edjg HYV GdeMHjf ef YQhb GdMRfHd hhQbg hRgQg hcCf GdoegpOj de jHjf dg HYV NhGUg MSH eYQaJg s
(3BNQgG (B:s
(3hYdi gPG ace TYjQGJ hce TYQGJ hce PQGI hce NTNGTGJ hce NQOdGJ aSHMGf ef dG jMUj YOO eNdhbGJg EdG gh heG jYde LfhO QHc EdG gh heG gj EdG PcQi ddHTQ hEf ef TjF EdG jSHM HMeOg JYGdi JeJs
(3Ydi bjO HNW GdeDda UhQJg (B: (3GdBeQ HJMQjQgG HYO EfTGFgG hJbQjQgG GdYHO GdCMbQ hGdYGLR GdCabQ eDdagG (B() (3GdgfOj Gdjefj GdCjhHj GdCfUGQj GdHNGQj YaG Yfg hYf hGdOjg Gdegjef GdHGQj ; Bejf , (B1306 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1/759s
(3eUGOQ GdacQ (B, (3GdMHTj (B1\590s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdcjejGA hGdWHjYjGJs